A Theoretical Analysis of ChatGPT Integration in Flipped Classrooms to Enhance Personal Learning Space - Risang Baskara (Universitas Pendidikan Ganesha, 2024)
This paper presents a theoretical analysis of the interconnection between ChatGPT, flipped classrooms, and personal learning spaces in higher education. The context of this research is the need to improve teaching and learning support in higher education through research and practice applicable to all disciplines and contexts. This research addresses the following questions: How can ChatGPT be integrated into flipped classrooms to enhance personal learning space? What can theoretical frameworks be used to support this integration? Previous research has shown that flipped classrooms can enhance students' learning outcomes and personal learning space by allowing them to learn at their own pace. However, there is a need for theoretical frameworks that can guide the integration of ChatGPT into flipped classrooms to enhance personal learning space. The primary rationale for this research is to explore theoretical frameworks that can support the integration of ChatGPT into flipped classrooms to enhance personal learning space. This is important because it can enhance students' learning outcomes and promote personalised learning experiences. The research methods used in this paper involve a systematic review of the literature on ChatGPT, flipped classrooms, and personal learning space, followed by a theoretical analysis of the interconnection between these concepts. The main findings of this paper suggest that the integration of ChatGPT into flipped classrooms can enhance personal learning space by providing personalised support and feedback to students. These findings imply that ChatGPT can promote personalised learning experiences and improve teaching and learning support in higher education.